2016
DOI: 10.1007/s12649-016-9599-9
|View full text |Cite
|
Sign up to set email alerts
|

Co-pyrolysis of Rice Husk with Underutilized Biomass Species: A Sustainable Route for Production of Precursors for Fuels and Valuable Chemicals

Abstract: In this study, co-pyrolysis of rice husk with underutilized biomass, Napier grass and sago waste was carried out in a fixed bed reactor at 600°C, 30°C/min and 5 L/min nitrogen flowrate. Two-phase bio-oil (organic and aqueous) was collected and characterized using standard analytical techniques. 34.13-45.55 wt% total boil-oil yield was recorded using assorted biomass compared to pure risk husk biomass with 31.51 wt% yield. The organic phase consist mainly benzene derivatives with higher proportion in the oil fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…From the reactor size and carrier gas flowrate reported by the authors, vapor residence was around 1.425 min (85 sec), which is long enough to result to severe secondary cracking of the pyrolysis vapor at such a high temperature. Some classical studies on the pyrolysis of Napier grass have also been reported by our research group recently (Mohammed et al, 2015b;Lim et al, 2015, Mohammed et al, 2016a, 2016b, 2016d, Lim et al, 2016. To date, no study on pyrolysis of Napier grass is available in the literature that deals with collective examination of pyrolysis temperature, heating rate, inert gas flowrate on the products distribution and composition.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…From the reactor size and carrier gas flowrate reported by the authors, vapor residence was around 1.425 min (85 sec), which is long enough to result to severe secondary cracking of the pyrolysis vapor at such a high temperature. Some classical studies on the pyrolysis of Napier grass have also been reported by our research group recently (Mohammed et al, 2015b;Lim et al, 2015, Mohammed et al, 2016a, 2016b, 2016d, Lim et al, 2016. To date, no study on pyrolysis of Napier grass is available in the literature that deals with collective examination of pyrolysis temperature, heating rate, inert gas flowrate on the products distribution and composition.…”
Section: Introductionmentioning
confidence: 80%
“…Characteristic of NGS used in this study is summarized in been reported that mineral composition of biomass has great influence on both product yield and bio-oil composition (Mohammed et al, 2016b). Most researchers employed x-ray fluorescence (XRF), energy dispersive x-ray (EDX) in determining the mineral composition of biomass.…”
Section: Feed Stock Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the intensity of the modified ZSM-5 decreased with increased NaOH concentration. This observation shows a loss of crystallinity due to desilication, which could also be linked to the formation of mesoporous structures in the material [34,35]. Physisorption analysis (Figure 3) of ZSM-5 displayed a type I isotherm according to the IUPAC classification.…”
Section: Characteristics Of Catalystsmentioning
confidence: 96%
“…Pyrolysis is regarded as promising technology for the production of bio-oils from biomass feedstock [1][2][3][4][5][6]. However, the bio-oils are viscous, highly oxygenated, acidic, chemically unstable, have higher water content and low H/C ratios [7].…”
Section: Introductionmentioning
confidence: 99%